Notes on slavery and human trafficking in early republican Peru - Chocano, Magdalena (2019)
This essay focuses on republican slavery in the context of the history of traffic of human beings in Peru. We examine the conditions which led to the struggle against slavery, the ambiguity appearing inside the early Peruvian state regarding this issue when slavery was partially abolished, as well as the resistance of landowners to this changes, the efforts of slaves and liberal groups to end the slave system and the general impact on the public space.